Book Review: White Rage by Carol Anderson - Condor, Roxana M. (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2019)
Book review of White Rage: The Unspoken Truth of Our Racial Divide. By Carol Anderson. New York: Bloomsbury USA, 2016. 304 pages. ISBN 9781632864130.